Effect of high and low flexibility levels on physical fitness and neuromuscular properties in professional soccer players - Rey, E.; Padron-Cabo, A.; Barcala-Furelos, R.; Mecias-Calvo, M. (International Journal of Sports Medicine, 2016)
This study aimed to analyse the impact of high and low flexibility levels of hamstring and quadriceps muscles on physical fitness and neuromuscular properties in professional soccer players. 62 male professional soccer players participated in this study and performed 2 instrumented flexibility tests (passive straight leg raise [PSLR] and quadriceps flexibility [QF]). Anaerobic performance was assessed using countermovement jump (CMJ), Abalakov vertical jump, 20-m sprint, and Balsom agility test. A k-means cluster analysis was performed to identify a cut-off value of hamstring and quadriceps flexibility and classify players as high hamstring flexibility (HHF) and low hamstring flexibility (LHF) or high quadriceps flexibility (HQF) and low quadriceps flexibility (LQF), respectively, according to the PSLR and QF performances. The LQF players performed better than HQF on CMJ (p=0.042, ES: 0.64) and Balsom agility test (p=0.029, ES: 0.68). In addition, LQF showed higher muscular stiffness than HQF players (p=0.002, ES: 0.88). There were no significant differences between HHF and LHF groups. When pooling the HQF and LQF players` data, the Pearson`s correlation showed significant moderate positive association between muscular stiffness and QF (r=0.516, p<0.001). These results support the rationale that baseline stiffness is likely to influence athletic performance rather than flexibility level in soccer players.